Melacak Jejak Sejarah Witte Kruis Kolonie Melalui Film Dokumenter - Yoga Tri Budi Utomo; Anthony Y.M Tumimomor (Student Research Journal, 2023)
Witte Kruis Kolomie was the first humanitarian colony in Salatiga in 1901. This humanitarian colony was founded by a European husband and wife who were moved because many people were sick, displaced due to the impact of the eruption of Mount Kelud and the disease outbreak in 1901. Humanitarian activities that took place at Witte Kruis Kolomie, which does not look at social status and religion, this is a social activity that today's society should be aware of. However, based on data searches, information about the Witte Kruis Kolomie is still very minimal, both written and audio visual. Apart from that, there is information that is not in accordance with the events or events that actually occurred at Witte Kruis Kolomie. Documentary films can be an information medium that is able to provide more up-to-date information and present accurate data. By applying qualitative methods and linear strategies in the process of designing this documentary film, it is hoped that we will be able to produce and present a documentary film with a historical genre that is interesting and provides as accurate information as possible regarding the social and humanitarian activities of the Witte Kruis Kolomie, which has existed since 1901 in Salatiga, to the audience. or society.